Errata for “Jozef Zwierzycki, a prolific Polish geological mapping expert in Indonesia, 1914 – 1938.” - J.T. (Han) van Gorsel; Alina Chrzastek; Anna Gorecka-Nowak (Berita Sedimentologi, 2021)
The two co-authors of the paper on Dr. J. Zwierzycki in Berita Sedimentologi 46, A. Chrzastek and A. Gorecka-Nowak requested of few corrections. None of these are related to the life and work of Dr. Zwierzycki during his time in Indonesia